The use of robots as mediators in psychoanalytical clinical practice with autistic children - Badaró, Stéphanie Alves Furtado; Pires Calzavara, Maria Gláucia (Clinical Styles. The Journal on the vicissitudes of childhood, 2021)
Our proposal, from the psychoanalytic clinic, is to demonstrate how the use of the robot, as a technological object, may allow the autistic child, in the treatment, greater interaction and bond with the Other. We place a bet that interventions mediated by the robot can provide a semblance of the subject's constitutive operations that have not taken place. Considering that the components of the autistic border allow the subject to bond in the social environment, the possibilities of 'widening' this autistic border are highlighted from qualified interventions with object. Thus, the use of the robot in the sessions makes the interventions less invasive to the child, allowing a certain drive regulation, favoring a privileged path of communication and intervention, producing greater social interaction.